A community-based participatory model for integrating lobster aquaculture into coastal tourism livelihoods - Perdanawati, Rizqi Abdi; Mauludiyah; Nugraha, Dimas Rizal Wahyu; Hadi, Moch Irfan; Violando, Wiga Alif (UIN Sunan Ampel Surabaya, 2025)
Bangsring Village, Banyuwangi Regency, Indonesia is a coastal tourism area with high ecological and economic potential; however, tourist visitation has declined significantly since 2020, highlighting the need for locally grounded and resilient livelihood innovations. This study aims to evaluate the feasibility and community relevance of lobster aquaculture as a tourism-supporting livelihood strategy using a Community-Based Participatory Research (CBPR) framework. The CBPR process was implemented through collaborative problem identification, participatory planning, joint environmental assessment, and community-led implementation involving the Pesona Bahari Community Group. Water quality parameters and site characteristics were jointly analyzed to inform technology selection. Based on these findings, a circular bottom (base) net-cage system was selected due to its suitability for moderate current conditions, benthic substrates, and its ability to mimic the natural habitat of lobsters. Program implementation included cage construction and deployment, seed stocking, daily maintenance using natural feed, and harvesting after approximately 100 days of rearing. The outcomes indicate increased community capacity in environmentally responsible lobster aquaculture practices and successful production of marketable-sized lobsters under local conditions. Beyond economic diversification, lobster farming activities also function as an educational and experiential attraction, strengthening the integration between aquaculture and coastal tourism. This study contributes a context-specific CBPR-based model for integrating small-scale lobster aquaculture with coastal tourism development. The approach demonstrates practical applicability and potential replicability for other coastal communities seeking sustainable livelihood diversification without compromising ecosystem integrity.